Karnataka Draft Annual Plan 1983-84 Part I: the Plan - Planning Commission (Planning Commission, 1983)
The Annual Plan for 1983-84 comes little more than half way in the Sixth Plan. Therefore while the basic framework of the Sixth Plan has been kept in view, a few changes have also been incorporated, based on the findings of a mid-term review. The National priorities for the Power and Irrigation Sectors have been kept in mind in the Annual Plan for 1983-84 since they apply to the State as well. Thb Plan reiterates the emphasis on the two basic problems of the State's economy, namely the problems of unemployment and poverty. Closely related is the problem of imbalances in development.
Government of Karnataka Planning Department